Foreign exchange derivative use and firm value: Evidence from German non-financial firms - Matthias F. Merkel (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2018)
In this paper I investigate whether the use of foreign exchange (FX) derivatives adds value to German firms, which together make up one of the major export economies in the world. I analyze a unique, hand-collected dataset that includes information on the use of FX derivatives by 391 firms between 2004 and 2013. After controlling for a set of fundamental firm characteristics I find that on average the use of FX derivatives does significantly add to their value. This relationship seems to be mainly driven by firms with low values, suggesting that such firms can increase their value by using these instruments. Analysis of the detailed information of my dataset shows that besides the simple decision to use derivatives, the intensity of firms' use of them is also positively linked to firm value. My results show that especially firms with high values can further increase their firm value by increasing their FX derivative holdings.
Keywords: F23; G15; G32; 650; FX derivatives; hedging; Tobin's Q; firm value